2022
DOI: 10.1002/ijc.34140
|View full text |Cite
|
Sign up to set email alerts
|

Immune‐related conditions and cancer‐specific mortality among older adults with cancer in the United States

Abstract: Immunity may play a role in preventing cancer progression. We studied associations of immune‐related conditions with cancer‐specific mortality among older adults in the United States. We evaluated 1 229 443 patients diagnosed with 20 common cancer types (age 67‐99, years 1993‐2013) using Surveillance Epidemiology and End Results‐Medicare data. With Medicare claims, we ascertained immune‐related medical conditions diagnosed before cancer diagnosis (4 immunosuppressive conditions [n = 3380 affected cases], 32 au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Among recipients, the elevated mortality from cancer is explained by their increased incidence for certain cancers and decreased survival after a cancer diagnosis, each of which is plausibly related to immunosuppression from medications used to prevent organ rejection. [1][2][3][4][5][6][7] Consistent with findings in other studies, [8][9][10] we also saw a decline in overall cancer mortality in more recent calendar years. Although this trend could reflect the effects of decreasingly intense immunosuppressive regimens in recent years, cancer incidence has not changed markedly over time.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Among recipients, the elevated mortality from cancer is explained by their increased incidence for certain cancers and decreased survival after a cancer diagnosis, each of which is plausibly related to immunosuppression from medications used to prevent organ rejection. [1][2][3][4][5][6][7] Consistent with findings in other studies, [8][9][10] we also saw a decline in overall cancer mortality in more recent calendar years. Although this trend could reflect the effects of decreasingly intense immunosuppressive regimens in recent years, cancer incidence has not changed markedly over time.…”
Section: Discussionsupporting
confidence: 91%
“…[1][2][3][4] In addition to increasing the risk for cancer, immunosuppression may impair response to cancer treatment because a history of solid organ transplantation among patients with cancer is associated with reduced survival from their cancer. [5][6][7] Many studies provide estimates of cancer incidence in recipients, [1][2][3] but it is also necessary to systematically evaluate cancer mortality. Cancer mortality is an important metric that quantifies the overall impact of cancer in a population, encompassing the effects of cancer incidence, response to cancer treatment, and survival after cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a national, matched cohort study with the United States (US) Veterans Health Administration database from 2000 to 2017, Johnson et al showed that approximately 15% of excess deaths in RA were attributed to lung cancer (adjusted HR 1.47 [95% CI 1.37–1.57] vs. non-RA patients) [ 10 ]. In a retrospective cohort study with the Surveillance, Epidemiology, and End Results-Medicare database in the US from 1993 to 2013, Wang et al showed that RA was associated with increased cancer-specific mortality among elderly patients with lung cancer (adjusted HR 1.13 [95% CI 1.09–1.16]) [ 42 ]. The present study was conducted in patients who developed lung cancer during 2006–2021, and the risk of lung cancer-related death was significantly higher in RA patients compared with non-RA patients (adjusted HR 2.49 [95% CI 1.65–4.79]).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency and distribution of individual autoimmune diseases in our cohort was as expected based on the population’s age and existing reports on preexisting autoimmune disease in MDS. 16 , 34 Defining the impact of autoimmune disease on MDS outcomes is important, given the sizable proportion of patients affected. Previous studies have shown discordant results; some suggest a favorable impact on survival, 15 , 16 whereas others found an adverse effect 13 , 14 or no effect.…”
Section: Discussionmentioning
confidence: 99%